Hybrid RFID System-based Pedestrian Localization: A Case Study - Wang, Haowei; Bauer, Georg; Kirsch, Fabian; Vossiek, Martin (10th Workshop on Positioning, Navigation and Communication 2013 (WPNC 2013), 2013)
Localization systems using RFID - especially passive RFID - are coming increasingly under the spotlight. Passive RFID has a relatively small sensing range compared to other radio-frequency-based localization techniques. Therefore in practice the deployed tags may not cover the whole scene of interest. Additionally, in the area of pedestrian localization, the unpredictable movement of pedestrians makes a complete RFID tag coverage extremely difficult. This paper introduces a hybrid RFID localization system used for indoor pedestrians to overcome the coverage shortfall associated with passive RFID tags. Two extra sources are used to assist the RFID system: local INS sensors and ZigBee nodes. A particle filter serves as a fusion framework. A test scenario was built with 220 RFID tags and 8 ZigBee nodes deployed in a museum. Different algorithms were evaluated in this deployment. The results show that the hybrid approach produces robust localization even with a low number of tags. © 2013 IEE
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.hybrid
Keywords: dead reckoning; fingerprinting; hybrid localization; particle filter; RFID

Optimization of Fusion Algorithm for Hybrid Pedestrian Localization and Navigation - Wang, Haowei; Bauer, Georg; Kirsch, Fabian; Vossiek, Martin (9th Workshop on Positioning, Navigation and Communication 2012 (WPNC 2012), 2012)
Hybrid pedestrian localization based on multiple data sources is becoming more and more popular. Nevertheless, accurate and reliable pedestrian localization is still a challenge due mainly to their unpredictable movement. For some applications such as interactive museum guidance unpredictable pedestrian movement is a major obstacle to accurate localization. In this paper we introduce a novel fusion algorithm using best-neighbor rating. The algorithm reduces the accumulated error originating from unreliable sensor measurements and increases the efficiency by only evaluating the nearby cells of the last estimated position. Experimental results show that a mean error of less than 1.5 M is achievable in real-world scenarios. © 2012 IEE
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEH.optimi
Keywords: Dead Reckoning; Inertial Sensor; Localization; Navigation; Sensor Fusion; ZigBee

Where is the Tag? - Miesen, Robert; Ebelt, Randolf; Kirsch, Fabian; Schäfer, Tobias; Li, Gang; Wang, Haowei; Vossiek, Martin (IEEE Microwave Magazine, 2011)
Radio-frequency identification (RFID) localization developments and trends are reviewed. RFID localization relative to a reader can be broken down into two different tasks: ranging and direction finding. A system with both of these capabilities can provide two-dimensional (2-D) or three-dimensional (3-D) localization and an RFID system with only one of these capabilities can still provide useful functionalities. Standard RFID systems feature only coarse locating capabilities with a granularity given by the dimension of a cell formed by a reader. RFID ranging techniques may be categorized according to three criteria. The first and second are the type of transponder and the fundamental principle behind tag localization. Broadband chipless RFID tags have emerged as very promising candidates for next generation locatable RFID transponder
lhft_intern.bib::Miesen2011c